Economic viability of sugarcane dry cleaning - Gonçales Filho, Manoel; Delboni, Clóvis; Silva, Reinaldo Gomes da; Campos, Fernando Celso de (Brazilian Journal of Production Engineering, 2020)
This article analyzes the economic and financial feasibility of a set of equipment necessary to replace the traditional process of cleaning sugarcane (using water) from Brazilian sugar-energy plants, with another dry one (blow-cleaning). Thus, the objective is to reduce or eliminate the use of water in the cleaning phase of sugar cane and, consequently, straw, once separated at the reception by the suggested cleaning method (puff), can be used as a source energy efficiency and improve process efficiency. The research started from an exploratory bibliographic review in the area of ​​Administration and Production Engineering, in which it allowed the identification of Economic Engineering tools that contributed to the economic and financial viability of investments, facilitating decision making. A multi-case study was carried out in four sugar-energy plants located in the interior of the State of São Paulo. Thus, it was possible to apply and analyze the results through the Internal Rate of Return on Investment and the Net Present Value, regarding the possibility of investment and of this equipment, contributing to the minimization of water use, and to better use of straw in the production process